STRATEGI KOMUNIKASI DINAS PEMUDA OLAHRAGA KEBUDAYAAN DAN PARIWISATA KABUPATEN SIDOARJO DALAM MEMPERKENALKAN WISATA CANDI DERMO - A, Novita Dewi; Zakariya, Zakariya (representamen, 2017)
This research was motivated by the importance of coordination and cooperation between theDisporabupar Sidoarjo regency with relevant parties in the implementation of promotional activitiesto introduce the Dermo Temple travel on public or tourists, both local, national, to international. TheDermo Temple is one of the historical heritage of Majapahit kingdom whose existence has been awhile but have not been exposed so well that needed effective communication strategy to restoretouristsâ€™ interest in travel the Dermo temple. The problem of this research is â€œHow is theCommunication Strategy Disporabudpar Sidoarjo Regency in introducing Dermo Temple travel?â€, inorder to determine the communication strategy Disporabudpar Sidoarjo in introducing Dermo Templetravel by using the theory of Communication Mix..But in practice Sidoarjo Regency Disporabudparnot maximize elements in Communication Mix for the implementation of promotional activities thatmay help the Disporabupar Sidoarjo district in introducing Temple Dermo travel. So it is advisable toget more leverage in conducting promotional activities and can be run it continuously and sustainablyto people or even tourists better understand and understand the sights promoted.Keyword : Communication Strategy, Disporabudpar, Dermo Temple.